THE MASTERPIECES OF ABDULLAH IBN MUBARAK - Akmal Ulugmurotov (Galaxy International Interdisciplinary Research Journal, 2021)
Ibn al-Nadim mentions the following books in the sixth chapter under the heading "Reports on the Fuqaha of the Companions of Hadith" as the books of Ibn al-Mubarak: 1. Kitab al-Sunan fil-Fiqh (Book on the Laws of Fiqh),2. “Kitab at-tafsir” (Book of Tafsir),3. “Kitab at-Tarikh” (History Book),4. “Kitab al-birri was-sila” (The Book of Doing Good and Compassion), 5. “Kitab az-zuhd var-raqaiq” (The Book of Piety and Theology)6. “Musnsd”, “Kitabu al-jihad”, “Arbain”.7. "Riqoul al-fatava".